Method for producing oxidized cellulose and cellulose nanofibers, oxidized cellulose and cellulose nanofibers, and food

By oxidizing unused biomass with hypochlorous acid to produce oxidized cellulose and then defibrating it, the method addresses the high cost and environmental issues of existing cellulose nanofiber production, achieving efficient and cost-effective cellulose nanofibers with low nitrogen content.

JP7605135B2Active Publication Date: 2024-12-24TOAGOSEI CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021571177
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-16
Filing Date
2021-01-08
Publication Date
2024-12-24
Estimated Expiration
2041-01-08

AI Technical Summary

Technical Problem

Existing methods for producing cellulose nanofibers from cellulose-based raw materials, such as wood pulp and soybean byproducts, face challenges including high cost, environmental toxicity from N-oxyl compounds, and inefficient protein removal, leading to economically unfavorable and environmentally harmful processes.

Method used

A method using unused biomass, such as soybean byproducts, is oxidized with hypochlorous acid or its salt to produce oxidized cellulose, which is then defibrated into cellulose nanofibers without N-oxyl compounds, reducing nitrogen content and protein contamination, and avoiding the use of strong acids like nitric acid.

Benefits of technology

This approach enables the production of cellulose nanofibers with low protein content at a lower cost, improving fibrillation efficiency and reducing environmental impact, making it economically viable and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605135000001
    Figure 0007605135000001
Patent Text Reader

Abstract

The present invention provides a method for producing cellulose oxide, comprising a step for producing cellulose oxide by reacting unused biomass with hypochlorous acid or a salt thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing oxidized cellulose and cellulose nanofibers, oxidized cellulose and cellulose nanofibers, and foods. [Background technology]

[0002] It is known that cellulose nanofibers are produced by mechanically defibrating cellulosic raw materials. Methods of producing cellulose nanofibers by oxidizing various cellulosic raw materials have also been studied. For example, Patent Document 1 discloses a method of oxidizing a cellulosic raw material with sodium hypochlorite, an oxidizing agent, in the presence of 2,2,6,6-tetramethylpiperidine-1-oxy radical (hereinafter referred to as TEMPO) and bromide.

[0003] Patent Document 2 discloses a method that does not use a catalyst such as TEMPO, in which various cellulosic raw materials are oxidized with sodium hypochlorite to produce cellulose nanofibers that have a carboxyl group content of 0.20 to 0.50 mmol / g relative to the dry mass of the cellulose nanofiber, an average fiber diameter of 3 to 100 nm, and do not contain N-oxyl compounds.

[0004] In order for cellulose nanofibers to be widely used for various applications, they need to be produced at low cost. However, wood-based pulp, which contains a large amount of cellulose and is commonly used as a cellulose-based raw material, is expensive and economically undesirable as a raw material for cellulose nanofibers.

[0005] Soybean by-products, which are a type of unused biomass from food manufacturing, include "okara," a by-product from the production of soy milk and tofu. The supply of okara as food far exceeds the demand, and its quality deteriorates quickly, so much of it is disposed of as industrial waste. The cost of processing it is a heavy burden on soy milk and tofu manufacturers. In addition, a large amount of "soybean hulls," a by-product from the extraction of oil from soybeans, is also generated, and processing it is also a problem. "Okara" and "soybean hulls" contain a large amount of cellulose and are inexpensive. Therefore, the use of unused biomass, including soybean by-products, as a raw material for cellulose nanofiber is being considered. For example, Patent Document 3 discloses a method for producing cellulose nanofibers using unused biomass as a raw material, in which unused biomass is mechanically defibrated. Patent Document 4 discloses a method in which plant biomass is contacted with an acid component containing nitric acid, and then reacted with an oxidizing agent such as nitrite or nitrate, followed by heating. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-155897 A [Patent Document 2] JP 2017-193814 A [Patent Document 3] JP 2003-155349 A [Patent Document 4] Special Publication No. 2018-533660 Summary of the Invention [Problem to be solved by the invention]

[0007] A wide range of cellulose-based raw materials are exemplified in the methods described in Patent Documents 1 and 2, including those derived from plant materials such as pulp and wood, animal materials, algae, and microorganisms, but the one specifically used is wood-based pulp. Patent Documents 1 and 2 do not specifically describe the production of cellulose nanofibers from raw materials derived from unused biomass such as soybean by-products using hypochlorous acid or a salt thereof.

[0008] In the oxidized cellulose produced using an N-oxyl compound such as TEMPO as a catalyst as described in Patent Document 1, even after thorough washing, several ppm of N-oxyl compounds remain as nitrogen. Because there are concerns about the toxicity of N-oxyl compounds to the environment and human body, when an aqueous dispersion of cellulose nanofibers is prepared using oxidized cellulose, N-oxyl compounds will also be present in the dispersion. When nanocellulose is used as a highly functional material, the N-oxyl compounds present in the dispersion may have undesirable effects depending on the application. In addition, since N-oxyl is a very expensive material, the method using N-oxyl cannot be said to be an economical production method.

[0009] In Patent Documents 3 and 4, soybean by-products are used as cellulosic raw materials, but Patent Document 3 describes a production method using only mechanical fiberization, while Patent Document 4 describes a method using nitric acid, which is a strong acid, and neither describes the oxidation of soybean by-products with hypochlorous acid or a salt thereof. Soybean by-products also contain proteins, so proteins are present in the cellulose nanofibers obtained only by mechanical defibration using the method of Patent Document 3. Proteins deteriorate over time and need to be removed, but there is a problem in that it is difficult to separate cellulose nanofibers from proteins. The method of Patent Document 4 generates wastewater containing nitrate nitrogen and nitrite nitrogen, and since this wastewater has a negative impact on the environment, it is necessary to carry out microbial treatment or the like, and there is a problem in that such treatment is very expensive.

[0010] In view of the above circumstances, the present invention aims to provide oxidized cellulose and cellulose nanofibers that use unused biomass as a raw material in a simple and efficient manner, as well as methods for producing the same. [Means for solving the problem]

[0011] As a result of intensive research to solve the above-mentioned problems, the inventors have discovered that it is possible to produce oxidized cellulose by using unused biomass as a raw material and hypochlorous acid or a salt thereof as an oxidizing agent, thereby oxidizing the unused biomass. They have also discovered that it is possible to produce cellulose nanofibers more simply and efficiently from unused biomass by defibrating the obtained oxidized cellulose.

[0012] That is, the present invention is as follows. [1] The method comprises a step of reacting unused biomass with hypochlorous acid or a salt thereof to produce oxidized cellulose. A method for producing oxidized cellulose. [2] The available chlorine concentration of the hypochlorous acid or its salt is 7% by mass or more and 43% by mass or less. A method for producing oxidized cellulose according to [1]. [3] The hypochlorous acid or a salt thereof is sodium hypochlorite. The method for producing oxidized cellulose according to [1] or [2]. [4] In the step of producing the oxidized cellulose, the reaction is carried out without using an N-oxyl compound. The method for producing oxidized cellulose according to any one of [1] to [3]. [5] The unused biomass is a food manufacturing by-product. The method for producing oxidized cellulose according to any one of [1] to [4]. [6] The nitrogen concentration in the oxidized cellulose is 3.0% by mass or less. The method for producing oxidized cellulose according to any one of [1] to [5]. [7] [1] to [6], the method for producing oxidized cellulose according to any one of the above, further comprising, after the step of producing oxidized cellulose, a step of defibrating the oxidized cellulose to obtain cellulose nanofibers. A method for producing cellulose nanofibers. [8] The average fiber length of the cellulose nanofibers is in the range of 100 nm or more and 800 nm or less, The average fiber diameter of the cellulose nanofibers is in the range of 1 nm to 10 nm. A method for producing cellulose nanofibers according to [7]. [9] Oxidized cellulose comprising an oxide of a cellulosic raw material with hypochlorous acid or a salt thereof, The oxidized cellulose, wherein the cellulosic raw material comprises unused biomass.

[10] An oxidized cellulose composition comprising the oxidized cellulose according to [9] and a solvent.

[11] [9] Cellulose nanofibers produced from the oxidized cellulose described in.

[12] A cellulose nanofiber composition comprising the cellulose nanofiber according to

[11] and a solvent.

[13] The oxidized cellulose composition according to

[10] , which is added to food.

[14] The cellulose nanofiber composition according to

[12] , which is added to food.

[15] A food product comprising the oxidized cellulose described in [9] and / or the cellulose nanofiber described in

[11] . Effect of the Invention

[0013] According to the present invention, it is possible to produce oxidized cellulose and cellulose nanofibers that are highly useful industrially from unused biomass that has not been effectively utilized until now. Furthermore, according to the present invention, it is possible to inexpensively produce cellulose nanofibers with a low protein content, making it an economically advantageous method for producing cellulose nanofibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, the components (including element steps, etc.) are not essential unless otherwise specified. The same applies to the numerical values ​​and their ranges, and they do not limit the present invention.

[0015] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0016] 1.Unused biomass In the present invention, the term "biomass" in the term "unused biomass" generally refers to renewable organic resources derived from living organisms, excluding fossil resources. Suitable examples of unused biomass include food manufacturing by-products, harvest residues, and non-edible food parts. In this specification, unused biomass raw materials such as food manufacturing by-products, harvest residues, and non-edible food parts are also referred to as edible cellulose raw materials.

[0017] Examples of food manufacturing by-products include soybean pulp, soy sauce lees, sake lees, beer lees, tea extract lees, vegetable or fruit lees, coffee grounds, sugarcane lees, seed oil cake, soybean oil cake, etc. Among these, soybean by-products are preferred, and soybean pulp is more preferred, from the viewpoint of containing a large amount of cellulose and being able to be supplied stably. Harvest residues refer to stems, leaves, vines, etc. remaining in a field after a crop has been harvested. Examples of harvest residues include rice, wheat, or barley straw, rice bran, rice husks, buckwheat husks, etc. In this specification, harvest residues also include crops that cannot be marketed due to poor size or shape, infestation by pests, etc. Inedible parts of food include, for example, the skins and leaves of vegetables or fruits.

[0018] When the unused biomass of the present invention is an edible cellulose raw material, the cellulose nanofibers produced from the unused biomass are suitable for food use, and specifically are useful as thickeners, dispersants, etc. in beverages, seasonings, health foods, etc.

[0019] The nitrogen concentration in unused biomass is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. By making the nitrogen concentration in utilized biomass 20% by mass or less, the nitrogen concentration in the oxidized cellulose or cellulose nanofibers can be reduced by reaction with hypochlorous acid or a salt thereof, and defibration efficiency can be improved. In the present invention, the nitrogen concentration in unused biomass means a value measured using an organic elemental analyzer. More specifically, it can be measured by the method described in the Examples.

[0020] 2. Method for producing oxidized cellulose The present invention relates to a method for producing oxidized cellulose, which comprises a step of reacting unused biomass with hypochlorous acid or a salt thereof to produce oxidized cellulose.

[0021] In the process of producing oxidized cellulose, unused biomass is oxidized using hypochlorous acid or a salt thereof. Oxidized cellulose can generally be obtained by reacting unused biomass in a liquid, preferably in water. The concentration of unused biomass in the liquid during the reaction is not particularly limited, but is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 5% by mass or less. The lower limit of the above concentration is usually sufficient as long as it exceeds 0% by mass, and may be 0.5% by mass or more, or 1% by mass or more. In addition, the effective chlorine concentration of hypochlorous acid or a salt thereof is not particularly limited, but is preferably 7 to 43 mass%. The lower limit of the effective chlorine concentration may be 8 mass% or more, 9 mass% or more, or 10 mass% or more. The upper limit of the effective chlorine concentration may be 40 mass% or less, or 35 mass% or less. When the effective chlorine concentration is 7 mass% or more, the reaction proceeds smoothly. When the effective chlorine concentration is 43 mass% or less, hypochlorous acid or a salt thereof is present stably. The effective chlorine concentration of hypochlorous acid or a salt thereof is more preferably 14 to 43 mass%.

[0022] The available chlorine concentration in hypochlorous acid or a salt thereof is a well-known concept and is defined as follows. Hypochlorous acid is a weak acid that exists only as an aqueous solution, and hypochlorites are compounds in which the hydrogen of hypochlorous acid has been replaced by another cation. For example, sodium hypochlorite, which is a hypochlorite salt, exists only in solution, so the amount of available chlorine in the solution is measured, rather than the concentration of sodium hypochlorite. The available chlorine in sodium hypochlorite is the oxidizing power of the divalent oxygen atom produced by the decomposition of sodium hypochlorite, which is equivalent to two atomic equivalents of monovalent chlorine. Therefore, the combined chlorine atoms in sodium hypochlorite (NaClO) have the same oxidizing power as two uncombined chlorine (Cl2) atoms, and available chlorine = 2 x (chlorine in NaClO). The available chlorine concentration can be measured by precisely weighing a sample, adding water, potassium iodide, and acetic acid, leaving the sample to stand, and titrating the liberated iodine with a sodium thiosulfate solution using an aqueous starch solution as an indicator. The available chlorine concentration can be measured specifically by the method described in the Examples.

[0023] Examples of hypochlorous acid or a salt thereof in the present invention include hypochlorous acid water, sodium hypochlorite, potassium hypochlorite, calcium hypochlorite, and ammonium hypochlorite. Among these, sodium hypochlorite is preferred from the viewpoint of ease of handling.

[0024] Hereinafter, the method for producing oxidized cellulose will be described using sodium hypochlorite as an example of hypochlorous acid or a salt thereof. Methods for adjusting the effective chlorine concentration of an aqueous sodium hypochlorite solution include concentrating an aqueous sodium hypochlorite solution with a low effective chlorine concentration, and adjusting the effective chlorine concentration by using sodium hypochlorite pentahydrate crystals with an effective chlorine concentration of approximately 43% by mass as is or by diluting them with water. The method for adjusting the effective chlorine concentration to the preferred range of 7 to 43 mass% includes the above-mentioned methods. Among these, it is preferable to use sodium hypochlorite pentahydrate as an oxidizing agent to adjust the effective chlorine concentration because it causes little self-decomposition, i.e., the effective chlorine concentration is less likely to decrease, and the adjustment is easy.

[0025] The amount of the aqueous sodium hypochlorite solution used as the oxidizing agent can be selected within a range that promotes the oxidation reaction. There are no particular limitations on the method for mixing unused biomass and the aqueous sodium hypochlorite solution, but from the standpoint of ease of operation, it is preferable to add unused biomass (aqueous solution) to the aqueous sodium hypochlorite solution and mix them.

[0026] The reaction temperature in the oxidation reaction is preferably 15 to 100°C, more preferably 20 to 90°C. In order to efficiently proceed with the oxidation reaction, it is preferable to maintain the pH of the reaction system at 5 or more, more preferably 6 or more, and further preferably 7 or more. There is no particular limitation on the upper limit of the pH, but it is preferably 14 or less. It is preferable to maintain the pH of the reaction system at 7 to 14. To adjust the pH, an alkali agent such as sodium hydroxide or an acid such as hydrochloric acid can be added as appropriate. The time for the oxidation reaction can be set according to the degree of progress of the oxidation, but it is preferable to carry out the reaction for, for example, about 15 minutes to 50 hours.

[0027] In the oxidation reaction, cellulose contained in unused biomass is oxidized to generate carboxyl groups to generate oxidized cellulose. The amount of carboxyl groups in the oxidized cellulose is not particularly limited, but when the oxidized cellulose is defibrated and nano-sized in the next step to produce cellulose nanofibers, the amount of carboxyl groups per 1 g of oxidized cellulose is preferably 0.2 to 3.0 mmol / g, more preferably 0.5 to 3.0 mmol / g. The oxidation reaction may be carried out in two or more stages.

[0028] In addition, since the unused biomass contains protein, for example, in order to remove the protein contained therein, filtration and washing with water may be performed after the oxidation reaction is completed. As the method of filtration and washing with water, a known method can be applied. The end point of the washing can be determined by comparing the electrical conductivity values ​​of the washing water and the washing wastewater.

[0029] The cellulose in soybean pulp, a type of unused biomass, is covered with other components (proteins, etc.), and it is thought that the oxidation reaction of N-oxyl compounds does not proceed because they are hindered by the proteins during the reaction. In contrast, when hypochlorous acid or its salts oxidize unused biomass, it is thought that the proteins, etc. are removed by sodium hypochlorite, and the oxidation of cellulose proceeds. Regarding raw materials that contain cellulose, in the case of wood-based pulp, cellulose twins are formed because components other than cellulose are removed during the manufacturing process, whereas cellulose twins are not formed in soybean pulp, which is a type of unused biomass.Since it is difficult for oxidizing agents to penetrate into cellulose twins, the oxidation rate is slow. For the above reasons, it is believed that the oxidation of cellulose in soybean pulp proceeds rapidly, and therefore, in the production method of the present invention, it is preferable to carry out the reaction without using an N-oxyl compound such as 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO).

[0030] 3. Manufacturing method of cellulose nanofiber The oxidized cellulose obtained in step 2 above can be defibrated and nano-sized to produce cellulose nanofibers. Therefore, one aspect of the present invention is a method for producing cellulose nanofibers, comprising the steps of reacting unused biomass with hypochlorous acid or a salt thereof to produce oxidized cellulose, and, after the step of producing the oxidized cellulose, subjecting the oxidized cellulose to a defibration treatment to obtain cellulose nanofibers. Here, the cellulose nanofiber includes nano-sized cellulose such as cellulose nanocrystals. Cellulose nanofibers and nano-sized cellulose such as cellulose nanocrystals are collectively referred to as nanocellulose. In the method for defibrating oxidized cellulose, the defibration time can be shortened by weak stirring in a solvent using a stirrer or by mechanical defibration, however, if the mechanical defibration is too strong, the cellulose nanofibers may break or be cut.

[0031] The method of mechanical defibration is not particularly limited, and can be appropriately selected depending on the purpose, for example, after washing the oxidized cellulose with a solvent, and examples include known mixing and / or stirring devices such as a screw mixer, a paddle mixer, a dispersion mixer, a turbine mixer, a homomixer under high speed rotation, a high pressure homogenizer, an ultra-high pressure homogenizer, a double cylindrical homogenizer, an ultrasonic homogenizer, a water flow opposing collision type disperser, a beater, a disk type refiner, a conical type refiner, a double disk type refiner, a grinder, and a single-shaft or multi-shaft kneader. By treating these materials alone or in combination with two or more types in a solvent, oxidized cellulose can be nano-sized to produce nanocellulose.

[0032] The solvent used in the defibration treatment is not particularly limited and can be appropriately selected depending on the purpose. Examples of the solvent include water, alcohols, ethers, ketones, carbonates, acetonitrile, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylsulfoxide. These may be used alone or in combination of two or more kinds.

[0033] Examples of alcohols include methanol, ethanol, isopropanol, isobutanol, sec-butyl alcohol, tert-butyl alcohol, methyl cellosolve, ethylene glycol, and glycerin. Examples of the ethers include ethylene glycol dimethyl ether, 1,4-dioxane, and tetrahydrofuran. Examples of the ketones include acetone and methyl ethyl ketone. Examples of carbonate esters include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, diphenyl carbonate, and ethyl methyl carbonate.

[0034] By selecting an organic solvent as the solvent, it becomes easy to isolate the oxidized cellulose obtained in the above process and the nanocellulose obtained by defibrating it. In addition, since the nanocellulose is obtained dispersed in the organic solvent, it becomes easy to mix it with the resin that dissolves in the organic solvent and the raw material monomer for the resin.

[0035] 4. Oxidized cellulose and cellulose nanofibers Oxidized cellulose and cellulose nanofibers can be obtained by the production method of the present invention. That is, one aspect of the present invention is oxidized cellulose comprising an oxidation product of a cellulosic raw material with hypochlorous acid or a salt thereof, the cellulosic raw material comprising unused biomass. Another aspect of the present invention is cellulose nanofibers produced from the above-mentioned oxidized cellulose. Specifically, the cellulose nanofiber of the present invention is a cellulose nanofiber obtained by defibrating oxidized cellulose containing an oxide of a cellulosic raw material using hypochlorous acid or a salt thereof, wherein the cellulosic raw material contains unused biomass.

[0036] The nitrogen concentration in the oxidized cellulose and cellulose nanofibers according to the present invention is preferably 3.0% by mass or less in either case. A nitrogen concentration of 3.0% by mass or less can improve defibration efficiency and make the shape of the cellulose nanofibers uniform. Therefore, the cellulose nanofibers of the present invention can be widely used in various applications. The nitrogen concentration is more preferably 2.0% by mass or less, and further preferably 1.0% by mass or less. The lower limit of the nitrogen concentration is ideally 0% by mass, but may be more than 0% by mass or may be 0.10% by mass or more. In the present invention, the nitrogen concentration of oxidized cellulose or cellulose nanofibers refers to a value measured using an organic elemental analyzer. More specifically, it can be measured by the method described in the examples.

[0037] As described above, the nitrogen concentration in unused biomass is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. The rate of change in the nitrogen concentration in oxidized cellulose or cellulose nanofibers relative to the nitrogen concentration in unused biomass (nitrogen concentration in oxidized cellulose or cellulose nanofibers / nitrogen concentration in unused biomass) is preferably 50% or less, more preferably 30% or less, and even more preferably 15% or less. A rate of change of 50% or less can improve defibration efficiency. The lower limit of the rate of change is ideally 0%, but may be more than 0% or may be 0.10% or more.

[0038] The average fiber length of the cellulose nanofibers according to the present invention is preferably 100 to 800 nm, more preferably 100 to 600 nm.The average fiber diameter of the cellulose nanofibers according to the present invention is preferably 1 to 10 nm, more preferably 1 to 5 nm. The average fiber width and average fiber length were calculated by mixing cellulose nanofibers with water so that the concentration of cellulose nanofibers was approximately 1 to 10 ppm, allowing the thoroughly diluted cellulose nanofiber aqueous dispersion to dry naturally on a mica substrate, observing the shape of the cellulose nanofibers using a scanning probe microscope, randomly selecting any number of fibers from the obtained image, and calculating the cross-sectional height of the shape image = fiber width and the circumference ÷ 2 = fiber length. Image processing software can be used to calculate the average fiber width and average fiber length. In this case, the image processing conditions are arbitrary, but the calculated values ​​may differ depending on the conditions even for the same image. The range of the value difference due to conditions is preferably within ±100 nm for the average fiber length. The range of the value difference due to conditions is preferably within ±10 nm for the average fiber width. For more detailed measurement methods, follow the methods described in the Examples below.

[0039] 5. Examples of use of oxidized cellulose and cellulose nanofiber The form of the oxidized cellulose and cellulose nanofibers of the present invention is not particularly limited, and may be a solid or a composition containing a solvent. Thus, one aspect of the present invention is an oxidized cellulose composition comprising the oxidized cellulose of the present invention and a solvent. Another aspect of the present invention is a cellulose nanofiber composition comprising the cellulose nanofiber of the present invention and a solvent. The oxidized cellulose or cellulose nanofiber composition of the present invention may contain at least oxidized cellulose or cellulose nanofibers and a solvent. These compositions may be in the form of a solution, a dispersion, or a suspension. The above-mentioned solvent is not particularly limited as long as it is a solvent that is generally used, and may be appropriately selected depending on the purpose for which the oxidized cellulose and cellulose nanofibers are used. Specific examples of the solvent include water, alcohols, ethers, ketones, carbonates, acetonitrile, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethylsulfoxide. Specific examples of the alcohols, ethers, ketones, and carbonates include the same compounds as those mentioned above. These may be used alone or in combination of two or more kinds.

[0040] As mentioned above, the cellulose nanofibers of the present invention can be included in foods, and the oxidized cellulose of the present invention may also be included in foods. Thus, one aspect of the present invention is a food product comprising the oxidized cellulose of the present invention or the cellulose nanofiber of the present invention. Furthermore, the above-mentioned oxidized cellulose composition or cellulose nanofiber composition can be added to food products. For food applications, the solvent contained in these compositions is preferably water and / or an alcohol such as ethanol. The content of oxidized cellulose or cellulose nanofibers in the oxidized cellulose composition or cellulose nanofiber composition of the present invention is not particularly limited, but may typically be from 0.1% to 50% by mass, alternatively from 0.1% to 30% by mass, alternatively from 0.1% to 20% by mass, or alternatively from 0.1% to 10% by mass, relative to the total amount of the composition. EXAMPLES

[0041] The present invention will be described in detail below with reference to examples and comparative examples. Various physical properties were measured by the following methods.

[0042] (Method for measuring the amount of carboxyl groups) Pure water was added to a 0.5% by mass slurry of oxidized cellulose to make up 60 mL, and a 0.1 M aqueous hydrochloric acid solution was added to adjust the pH to 2.5. After that, a 0.05 N aqueous sodium hydroxide solution was added dropwise and the electrical conductivity was measured until the pH reached 11. The electrical conductivity was calculated using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity was gradual. Amount of carboxyl groups (mmol / g oxidized cellulose) = a (mL) × 0.05 / mass of oxidized cellulose (g)

[0043] (Method for measuring nitrogen content in oxidized cellulose) The residual protein in the oxidized cellulose was measured as the nitrogen concentration in the oxidized cellulose using an organic elemental analyzer JM11 manufactured by J Science Labs. The nitrogen concentration in the raw material, soybean pulp, was 3.66% by mass.

[0044] (Method for measuring the average fiber length and average fiber diameter of cellulose nanofibers) The obtained dispersion was diluted 1,000 to 10,000 times with pure water, allowed to dry naturally on a mica substrate, and the shape of the cellulose nanofibers was observed in AC mode using an Oxford Asylum scanning probe microscope “MFP-3D infinity.” The average fiber length was analyzed by binarizing the obtained images using the image processing software "ImageJ." The number-average fiber length was calculated for 100 fibers as fiber length = "perimeter" ÷ 2. The average fiber diameter was calculated by using the software provided with the "MFP-3D infinity" to determine the number-average fiber diameter for 50 fibers, taking the cross-sectional height of the shape image as the fiber diameter.

[0045] <Example 1> In a beaker, sodium hypochlorite pentahydrate was dissolved in pure water to prepare 260 g of an aqueous sodium hypochlorite solution with an effective chlorine concentration of 21% by mass, and then hydrochloric acid was added to adjust the pH to 11. While stirring this liquid with a stirrer, soybean pulp powder (1.5 g) was added, and the mixture was stirred at 30° C. for 30 minutes to cause a reaction. During the reaction, sodium hydroxide was added dropwise to adjust the pH to 11. After the reaction was completed, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with 0.1 μm mesh, and the filtered product was washed with pure water and then the amount of carboxyl groups was measured. The amount of carboxyl groups was 1.24 mmol / g, and the amount of the filtered product (oxidized cellulose) was 0.30 g.

[0046] The available chlorine concentration in the aqueous sodium hypochlorite solution was measured by the following method. (Measurement of available chlorine concentration in sodium hypochlorite solution) 0.582g of an aqueous solution of sodium hypochlorite pentahydrate crystals added to pure water was precisely measured, 50ml of pure water was added, 2g of potassium iodide and 10ml of acetic acid were added, and the solution was immediately sealed and left in a dark place for 15 minutes. After leaving it for 15 minutes, the liberated iodine was titrated with 0.1mol / L sodium thiosulfate solution (indicator: starch test solution), and the titration amount was 34.55ml. A blank test was performed separately to correct the amount, and 1ml of 0.1mol / L sodium thiosulfate solution corresponds to 3.545mgCl, so the available chlorine concentration in the sodium hypochlorite aqueous solution is 21% by mass.

[0047] Pure water was added to the above-mentioned filtrate (oxidized cellulose) to prepare 20 g of a 1% by mass aqueous dispersion, which was then defibrated for 40 minutes using a Hielscher "UP-400S" ultrasonic homogenizer under conditions of CYCLE 0.5 and AMPLITUDE 50 to obtain a dispersion containing cellulose nanofibers. The obtained dispersion was observed by transmission phase contrast using an optical microscope LV100ND manufactured by Nikon Corporation, and no solid matter on the order of μm was observed.

[0048] The obtained dispersion was diluted 1000 times with pure water and allowed to dry naturally on a mica substrate. The shape was observed according to the method described above (method for measuring the average fiber length and average fiber diameter of cellulose nanofibers). As a result, cellulose nanofibers with an average fiber diameter of 3 nm and an average fiber length of 300 nm were confirmed.

[0049] <Example 2> Ethylene carbonate was added to the filter cake obtained in the oxidation reaction of Example 1 and heated to prepare 1 L of a 1% by mass dispersion at 65°C. The mixture was passed five times through a grinding machine "Supermasscolloider" manufactured by Masuko Sangyo Co., Ltd. to perform pre-fibrillation. 0.75 L of the above was defibrated 50 times using a Sugino Machine ultra-high pressure homogenizer "Starburst Lab" at 60-70°C and 200 MPa to obtain a dispersion containing cellulose nanofibers. The obtained dispersion was observed by transmission phase contrast in the same manner as in Example 1, and no solid matter at the μm level was found. When observed by a scanning probe microscope, cellulose nanofibers with an average fiber diameter of 3 nm and an average fiber length of 400 nm were observed.

[0050] <Example 3> The same conditions as in Example 1 were used, except that the contact time with sodium hypochlorite was 10 minutes.

[0051] <Example 4> The same conditions as in Example 1 were used, except that the contact time with sodium hypochlorite was 60 minutes.

[0052] <Example 5> The same conditions as in Example 1 were used except that the available chlorine concentration of sodium hypochlorite was 7 mass % and the contact time was 300 minutes.

[0053] <Comparative Example 1> Pure water was added to the soybean pulp powder, which was the raw material of Example 1, so that the amount was 1% by mass, and the mixture was defibrated using an ultrasonic homogenizer in the same manner as in Example 1. Observation under an optical microscope confirmed lumps of several tens of μm in size, indicating that they could not be defibrated by ultrasonic treatment alone.

[0054] <Comparative Example 2> 0.024 g of 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO) and 0.15 g of sodium bromide were dissolved in 150 g of pure water. 1.5 g of soybean pulp powder was added thereto, and then sodium hydroxide solution was added to adjust the pH to 10. While stirring this liquid, 3.75 ml of 2M sodium hypochlorite solution was added little by little, and the mixture was stirred and reacted at 25°C for 2 hours. During the reaction, the pH was maintained at 10 by adding sodium hydroxide solution dropwise. After the reaction, the product was subjected to solid-liquid separation by suction filtration using a PTFE membrane filter with a mesh size of 0.1 μm, and the filtered product was washed with pure water and then the amount of carboxyl groups was measured. The amount of carboxyl groups was 0.51 mmol / g, and the amount of the filtered product was 0.90 g. The nitrogen concentration in the obtained oxidized cellulose was 3.2 mass%, indicating that the nitrogen content was not significantly reduced compared to the raw material. Pure water was added to the residue on the filter to prepare 20 g of a 1% by mass aqueous dispersion, which was then defibrated for 40 minutes using a Hielscher "UP-400S" ultrasonic homogenizer under conditions of CYCLE 0.5 and AMPLITUDE 50 to obtain a dispersion containing cellulose nanofibers. The obtained dispersion was observed by transmission phase contrast using a Nikon LV100ND optical microscope, and clumps of several tens of microns were confirmed, indicating insufficient defibration. It is believed that defibration with residual protein reduces the defibration efficiency and also results in an uneven shape of the cellulose nanofibers.

[0055] <Comparative Example 3> (Production of cellulose nanofibers using wood pulp as raw material) The experiment was carried out under the same conditions as in Example 1, except that softwood pulp (Sigma-Aldrich, NIST RM 8495, bleached kraft pulp) in the form of flocculent was used instead of soybean pulp. The amount of carboxyl groups was 0.44 mmol / g, and the amount of material on filtration was 1.33 g. From this result and the result of Example 1, it was found that the oxidation rate was higher when soybean pulp was used as the raw material (soybean pulp: 1.24 mmol / g, pulp: 0.44 mmol / g per 30 minutes). It was thought that the oxidation rate would be slow because proteins would interfere with the oxidation, but the opposite result was obtained.

[0056] [Table 1]

[0057] This application claims priority to Japanese application No. 2020-005005, filed on January 16, 2020, and incorporates by reference all of the contents of that Japanese application. [Industrial Applicability]

[0058] The production method of the present invention obtains cellulose nanofibers by utilizing unused biomass, and the obtained cellulose nanofibers have high industrial utility. The present invention has industrial applicability, particularly in the field of food.

Claims

1. A method for producing oxidized cellulose, comprising a step of producing oxidized cellulose by reacting unused biomass with hypochlorous acid or a salt thereof, The unused biomass contains cellulose and protein, In the step of producing the oxidized cellulose, the reaction is carried out without using an N-oxyl compound, the nitrogen concentration in the oxidized cellulose is 0.10% by mass or more, a rate of change in the nitrogen concentration in the oxidized cellulose relative to the nitrogen concentration in the unused biomass (nitrogen concentration in oxidized cellulose / nitrogen concentration in unused biomass) is 15% or less; Manufacturing method.

2. The available chlorine concentration of the hypochlorous acid or its salt is 7% by mass or more and 43% by mass or less. The method for producing oxidized cellulose according to claim 1.

3. The hypochlorous acid or a salt thereof is sodium hypochlorite. The method for producing oxidized cellulose according to claim 1 or 2.

4. The unused biomass is a food manufacturing by-product. The method for producing oxidized cellulose according to any one of claims 1 to 3.

5. The nitrogen concentration in the oxidized cellulose is 3.0% by mass or less. The method for producing oxidized cellulose according to any one of claims 1 to 4.

6. A method for producing cellulose nanofibers, comprising, after the step of producing oxidized cellulose in the method for producing oxidized cellulose according to any one of claims 1 to 5, a step of defibrating the oxidized cellulose to obtain cellulose nanofibers.

7. The average fiber length of the cellulose nanofibers is in the range of 100 nm or more and 800 nm or less, and the average fiber diameter of the cellulose nanofibers is in the range of 1 nm or more and 10 nm or less. The method for producing cellulose nanofibers according to claim 6.

8. Oxidized cellulose containing an oxide of a cellulosic raw material by hypochlorous acid or a salt thereof (excluding oxidized cellulose containing an oxide of a cellulosic raw material by an N-oxyl compound), The cellulosic raw material comprises unused biomass, The oxidized cellulose, wherein the unused biomass contains cellulose.

9. 9. An oxidized cellulose composition comprising the oxidized cellulose of claim 8 and a solvent.

10. Cellulose nanofibers produced from the oxidized cellulose of claim 8.

11. A cellulose nanofiber composition comprising the cellulose nanofiber of claim 10 and a solvent.

12. 10. The oxidized cellulose composition of claim 9, which is added to food.

13. The cellulose nanofiber composition according to claim 11, which is added to food.

14. A food product comprising the oxidized cellulose of claim 8 and / or the cellulose nanofiber of claim 10.

Citation Information

Patent Citations

  • Inhibitor for rise in cholesterol and health food containing said inhibitor

    JP1985146828A

  • Water-based paste composition and its production

    JP1991058770A

  • Nano meter unit ultramicro fiber from natural organic fiber

    JP2003155349A

  • Cello-uronic acid and method for producing the same

    JP2009298968A

  • Cellulose material and laminate thereof

    JP2011068799A